Tailoring mesoporous silica nanomaterials from molecular simulation: Modelling the interplay of condensation reactions, surfactants and space-fillers during self assembly - Becit, Bahanur; Zahn, Dirk (Microporous and Mesoporous Materials, 2021)
We outline a coarse-grained model of silica nanoparticles, hexadecetyltrimethylammonium bromide surfactants and triamethylbenzene spacers for the analysis of mesoporous silica nanomaterials (MSN) formation from molecular simulation. Starting from random configurations, molecular dynamics simulations of annealing an artificial melt allow the unprejudiced investigation of silica-surfactant/spacer self-assembly. In analogy to the experimental syntheses protocol, the second step consists of removing the spacer and surfactant species from the system, followed by condensation reactions between the silica precursors. In our coarse-grained model, this intergrowth of the silica network is described by effective potentials that mimic atomistic simulations based on quantum/classical approaches. On this basis, rapid screening of pore structures as functions of surfactant and spacer concentration is demonstrated. After characterization of the self-organization process, we finally backmap the coarsened models into atomic structures, now enabling the detailed analyses of MSN loading by guest molecules - as illustrated for gemcitabine and ibuprofen, respectively.
CRIS-Team WoS Importer:2021-06-04